Prevalence and Associated Factors of Obesity in Children Aged 2-11 Years at a Tertiary Care Hospital in Islamabad: Prevalence and Associated Factors of Obesity in Children Aged 2-11 Years - Assadullah, .; Vaqar, Abeer; Vaqar, Rida; Bosan, Muddassir Altaf; Khan, Moiz; Zaman, Bakhat (Pakistan Journal of Health Sciences, 2025)
Childhood obesity is a rising health concern globally, with an increasing trend in many low middle-income countries like Pakistan, due to rapid urbanization and lifestyle changes like unhealthy dietary practices and lack of physical activity. Objectives: To find out the prevalence of obesity and some associated variables, such as demographic, socioeconomic, and lifestyle factors, among the children aged 2 to 11 years visiting a tertiary care hospital in Islamabad, Pakistan. Methods: The study was conducted from May 10, 2024, to November 10, 2024, at the Pediatric Department of the Avicenna Medical Complex in Islamabad. 220 children aged 2-11 years were recruited using consecutive sampling. Obesity was defined as a BMI ≥ +2SD on WHO percentile charts, and data related to its associated factors were collected. SPSS version 26.0 was used to analyze data and report descriptive statistics; chi-square tests were performed to determine statistical significance. Results: The prevalence of obesity was 7% (n=15). Among participants, 57% were aged 2-6 years, 59% were male, and 63% resided in rural areas. An insignificant association was found between obesity and age, gender, socioeconomic status, or family history (p>0.05). A higher obesity trend was observed in urban areas (11%) than rural areas (4%), though it was statistically insignificant (p=0.0538). Most of the children were physically active (88%), with high obesity (54%) reported in inactive children. Conclusions: Childhood obesity was low, with no significant associations found with key demographic or socioeconomic factors. However, urban residence and physical inactivity showed trends toward higher obesity risk.